Roles, Rules, and Controls: An Analytical Review of the Governance of Social Protection in Egypt - Kassem, Nada (AUC Knowledge Fountain, 2021)
This study examines the governance of social protection in Egypt. In light of rising poverty rates and economic and political instability, the government of Egypt has started shifting part of its focus towards reforming the social protection system, especially after the revolution in 2013. Because economic reforms have not translated in household income growth and since the currency devaluation have worsened socio-economic conditions, it is crucial and timely to examine the social protection arena in Egypt, focusing predominantly on the conditions and challenges of the governance of the system. This study adopts a framework that identifies three operational entry points of governance— Rules, Roles and Controls— as well as two spheres of analysis— program and sector levels. Twelve in-depth interviews with policy-makers and experts in relevant governmental, international and non-governmental bodies are used. The analysis focuses on the level of the social protection system as a whole and the program level, by examinig the contributory social insurance system as well as the non-contributory cash transfer programs, Takaful and Karama. Although Egypt has reformed the legislative framework of the social protection system, this analysis finds that the system still faces a number of shortcomings. Social protection in Egypt is confronted with the challenge of inadequate inter-ministerial coordination which hampers the establishment of a comprehensive, coherent and sustainable system that achieves social justice. The programs show a disconnect between design and implementation. Indeed, the two programs have designed and developed an adequate institutional infrastructure and monitoring and evaluation capacity. However, they face diverse implementation challenges. The recommendations of this analysis center around the establishment of an institutional home for social protection, the establishment of a common vision, the development of the necessary institutional and administrative capacity, a rigorous monitoring and evaluation toolkit, undergoing regular governance examinations, among others.